Potential Role of Plasmalogens in the Modulation of Biomembrane Morphology - Almsherqi, Zakaria A. (Frontiers in Cell and Developmental Biology, 2021)
Plasmalogens are a subclass of cell membrane glycerophospholipids that typically include vinyl- ether bond at the sn-1 position and polyunsaturated fatty acid at the sn-2 position. They are highly abundant in the neuronal, immune, and cardiovascular cell membranes. Despite the abundance of plasmalogens in a plethora of cells, tissues, and organs, the role of plasmalogens remains unclear. Plasmalogens are required for the proper function of integral membrane proteins, lipid rafts, cell signalling, and differentiation. More importantly, plasmalogens play a crucial role in the cell as an endogenous antioxidant that protects the cell membrane components such as phospholipids, unsaturated fatty acids, and lipoproteins from oxidative stress. The incorporation of vinyl-ether linked with alkyl chains in phospholipids alter the physicochemical properties (e.g., the hydrophilicity of the headgroup), packing density, and conformational order of the phospholipids within the biomembranes. Thus, plasmalogens play a significant role in determining the physical and chemical properties of the biomembrane such as its fluidity, thickness, and lateral pressure of the biomembrane. Insights on the important structural and functional properties of plasmalogens may help us to understand the molecular mechanism of membrane transformation, vesicle formation, and vesicular fusion, especially at the synaptic vesicles where plasmalogens are rich and essential for neuronal function. Although many aspects of plasmalogen phospholipid involvement in membrane transformation identified through in vitro experiments and membrane mimic systems, remain to be confirmed in vivo, the compiled data show many intriguing properties of vinyl-ether bonded lipids that may play a significant role in the structural and morphological changes of the biomembranes. In this review, we present the current limited knowledge of the emerging potential role of plasmalogens as a modulator of the biomembrane morphology.